An Ethnoscience Exploration of Terbang Gembrung Percussion From Kampung Naga, West Java and the Potential as Local Context in Physics Education - Sarah, Lia Laela; Liliawati, Winny; Sriyati, Siti (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This research aims to explore the ethnoscience of the Terbang Gembrung percussion instrument of the indigenous community in Kampung Naga, Tasikmalaya, West Java, and its potential as a local context in physics education. The Terbang Gembrung percussion instrument of Kampung Naga employs an acoustic membrane of goat leather with an air column of albasia or manglid wood. The research methodology encompasses qualitative descriptive methods, including literature study and interviews, as well as observation methods involving the measurement of sound frequency generated using the Decibel X smartphone application under conditions where the instrument produces typical sound. The Terbang Gembrung tradition holds religious value and is commonly performed during significant celebrations such as Eid al-Fitr, Eid al-Adha, and other religious festivities. Based on the observation results, it was found that four types of percussion instruments produce sound frequencies at four harmonic levels according to the membrane size. The first harmonic has a frequency of approximately 199.0 Hz, the second harmonic around 211.5 Hz, the third harmonic approximately 231.5 Hz, and the fourth harmonic around 261.0 Hz. The design of the percussion instrument is in the form of a half-spherical cone, with the cross-sectional area decreasing from the membrane to the end of the air column. The potential application of science principles to the Terbang Gembrung percussion instrument makes it a cultural artifact that can serve as a local context in physics education at the high school level, focusing on the topics of sound waves, especially sound intensity and sound frequency.